Delayed Healing Associated with Silver Sulfadiazine Use for Partial Thickness Scald Burns in Children. Issue 6 (June 2018) - Raymond, Steven L.; Zecevic, Antonia; Larson, Shawn D.; Ruzic, Ana; Islam, Saleem
Burns are a leading cause of injury in children. Management principles vary widely, with no consensus about the best treatment. The purpose of this study was to compare outcomes of three different dressings for pediatric partial-thickness scald burns. A retrospective, single-center study was conducted for patients 0–16 years old with a diagnosis of acute partial-thickness scald burn between July 2007 and December 2012. Data regarding prehospital, inpatient, and outpatient course were collected. Cohort was stratified into topical antimicrobial (TA) ointment, silver sulfadiazine (SS), and biosynthetic dressing (BD) groups for analysis. The primary outcome of interest was time to full healing. One hundred and seventy-seven patients met all study criteria. Overall, mean total body surface area burned was 8.3 per cent. TAwas used in 24 per cent cases, SS in 32 per cent, and BD in 44 per cent. The groups were comparable in terms of presenting burn characteristics and hospital course with the exception of the BD group being associated with greater extent of injury. Patients treated with SS had a significantly longer time to full healing and increased requirement of compression garments for scar therapy. Based on these data, the authors have amended their practice and presently use BD or TA dressings to improve healing.